Exploring Male and Female Voices through Epistemic Modality and Evidentiality in Some Modern English Travel Texts on the Canaries - Alonso-Almeida, Francisco; González-Cruz, Mª Isabel (Research in Language, 2012)
This article describes authorial voice through evidential and epistemic sentential devices in a corpus of 19th and early 20th century travel texts. The corpus contains four works written by female travellers and the other four by men. Therefore, apart from providing a catalogue of the strategies deployed by the authors in order to mark modality and evidentiality, we also report on expected differences in their frequencies of use in relation to the writer’s gender. In addition, the interest of this study lies in the fact that, to the best of our knowledge, no research on writer stance has previously been carried out in texts belonging to the genre of travel writing.